PENINGKATAN PENGETAHUAN DAN MOTIVASI PADA SISWA SD/MI TERDAMPAK PANDEMI DENGAN PENDAMPINGAN BELAJAR RUMAH PINTAR DI BANDUNG BARAT - Fikri Rizkia Muhammad (Jurnal Al Maesarah, 2022)
Education during the covid-19 pandemic brought a very big change from face-to-face learning in class to "back-to-back" learning or online learning at home, this must be done to suppress the spread of covid-19. In its implementation, there are many supporting and inhibiting factors, both internal and external, from teachers, students, parents and the community. The smart home program which is carried out in the context of community service aims to support the learning process in increasing knowledge and motivation in children at the SD/MI level while at the same time easing the burden on parents. This program is implemented in collaboration between lecturers and students participating in KKN STAI Darul Falah, West Bandung. In this smart home program applying learning assistance, motivation, providing basic material, memorization, exercises and games. The method used is a direct or expository learning method carried out face-to-face both in the home room, home page and open space. The media used in this program are textbooks to support SD/MI, stationery equipment, laptops and play equipment. The results achieved from this program are enthusiastic from the students, so this program runs well from the first week to the last week, so that students' knowledge increases and new experiences in learning are obtained by students.